Westonci.ca is the best place to get answers to your questions, provided by a community of experienced and knowledgeable experts. Connect with a community of experts ready to help you find accurate solutions to your questions quickly and efficiently. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.

Solve each system of equations by substitution. Clearly identify your solution.

Solve Each System Of Equations By Substitution Clearly Identify Your Solution class=

Sagot :

Space

Answer:

(0, 2)

General Formulas and Concepts:

Pre-Algebra

Order of Operations: BPEMDAS

  1. Brackets
  2. Parenthesis
  3. Exponents
  4. Multiplication
  5. Division
  6. Addition
  7. Subtraction
  • Left to Right

Distributive Property

Equality Properties

  • Multiplication Property of Equality
  • Division Property of Equality
  • Addition Property of Equality
  • Subtraction Property of Equality

Algebra I

  • Coordinates (x, y)
  • Terms/Coefficients
  • Solving systems of equations using substitution/elimination

Step-by-step explanation:

Step 1: Define Systems

y = x + 2

3x + 3y = 6

Step 2: Solve for x

Substitution

  1. Substitute in y [2nd Equation]:                                                                         3x + 3(x + 2) = 6
  2. [Distributive Property] Distribute 3:                                                                 3x + 3x + 6 = 6
  3. Combine like terms:                                                                                         6x + 6 = 6
  4. [Subtraction Property of Equality] Subtract 6 on both sides:                        6x = 0
  5. [Division Property of Equality] Divide 6 on both sides:                                  x = 0

Step 3: Solve for y

  1. Substitute in x [1st Equation]:                                                                           y = 0 + 2
  2. Add:                                                                                                                   y = 2

Answer:

(0, 2)

Step-by-step explanation:

Since y is x + 2, we can replace y with x + 2

3x + 3y = 6

3x + 3(x+2) = 6

3x + 3x + 6 = 6

6x + 6 = 6

6x = 0

x = 0

y = x + 2

y = 2

Now we can check by replacing x with 0

3x + 3y = 6

3(0) + 3y = 6

0 + 3y = 6

3y = 6

y = 2